A microdeletion encompassing PHF21A in an individual with global developmental delay and craniofacial anomalies. (3rd September 2015) - Labonne, Jonathan D. J.; Vogt, Julie; Reali, Lisa; Kong, Il‐Keun; Layman, Lawrence C.; Kim, Hyung‐Goo
Abstract : In Potocki–Shaffer syndrome (PSS), the full phenotypic spectrum is manifested when deletions are at least 2.1 Mb in size at 11p11.2. The PSS‐associated genes EXT2 and ALX4, together with PHF21A, all map to this region flanked by markers D11S1393 and D11S1319. Being proximal to EXT2 and ALX4, a 1.1 Mb region containing 12 annotated genes had been identified by deletion mapping to explain PSS phenotypes except multiple exostoses and parietal foramina. Here, we report a male patient with partial PSS phenotypes including global developmental delay, craniofacial anomalies, minor limb anomalies, and micropenis. Using microarray, qPCR, RT‐qPCR, and Western blot analyses, we refined the candidate gene region, which harbors five genes, by excluding two genes, SLC35C1 and CRY2, which resulted in a corroborating role of PHF21A in developmental delay and craniofacial anomalies. This microdeletion contains the least number of genes at 11p11.2 reported to date. Additionally, we also discuss the phenotypes observed in our patient with respect to those of published cases of microdeletions across the Potocki–Shaffer interval. © 2015 Wiley Periodicals, Inc.